Development of a toxicophenomic index for trace element ecotoxicity tests using the halophyte Juncus acutus: Juncus-TOX - Duarte, Bernardo (2021)
Marine and coastal ecosystems are the ultimate sink of many contaminants from anthropogenic activities, such as trace elements. Although several ecotoxicological tests are available using autotrophic organisms, none focus on marine plants. Juncus acutus has already showed that it is a good candidate for ecotoxicological studies, providing a good set of contamination biomarkers. The present work evaluates the application of pulse amplitude modulated (PAM) fluorometry derived variables to develop an integrated biomarker response index (Juncus-TOX) and classify the exposure of J. acutus seedlings to trace element contamination. Trace element exposure (Zn, Cu, Cd, Ni, Pb, and As) led to reduced seedling growth, confirming the toxic effects imposed by the tested elements and concentrations. Observing the Kautsky curves derived from each metal exposure, an abrupt fluorescence decrease could be observed at high Cu, Pb and Ni concentrations, while As exposure caused a modification in the shape of the Kautsky curve, by increasing the intensity of the J-step. These changes have consequences in the whole variable dataset extracted from the Kautsky curves. With the exception of the seedlings exposed to Zn, the generated variables proved to be good classifiers of the level of exposure to which the plants were subjected. Moreover, the phenomological energy fluxes attained from this bio-optical approach highlight the photobiological impacts of the different trace elements, which together with metal-substituted chlorophyll generation, support the observed morphometric changes. Cadmium and As exposure increased significantly the absorbed and dissipated energy fluxs (ABS/CS and DI/CS). Regarding the trapped and electron transport energy flux (TR/CS and ET/CS) there was a substantial decreased in the seedlings exposed to the highest concentrations of Cu, Ni and Pb. The 42 bio-optical parameters extracted from the JIP-test were included in a toxicophenomic index (Juncus-TOX). All the computed index versions showed good correlations with the exogenous trace element dose. Thus, Juncus-TOX proved to be an efficient tool for application in ecotoxicological assays using J. acutus, highlighting the potential use of this species as a future halophyte model species for ecotoxicology.